Encouraging Factors For Women's Empowerment In Community Care And Social Work - Suryani, Adi; Moh Saifulloh; Siti Zahrok; Soedarso; Zainul Muhibbin; Eka Dian Savitri (Aplikasi Administrasi: Media Analisa Masalah Administrasi, 2023)
Women are often seen as inferior to males in the community. Their occupations are limited to domestic duties such as caring for the family and making sure that everyday necessities are met. Despite their undervalued values, women continue to play a critical role in guaranteeing the welfare of the community, the well-being of the family, and the healthy development of the children. Nowadays, many women are joining the workforce, taking on leadership positions and taking part in a variety of community activities. This demonstrates the importance of women as contributors to society and the need to develop women's potential. Therefore, the study's goal is to investigate factors facilitating women's spiritual empowerment for treating female corpses. The study is focused on women empowerment at Desa Punggul by adopting qualitative method. The data are collected through participant direct observation and facilitating team's documentation, which are collected during community service program. The collected data are analyzed by using thematic analysis method. The study finds that women spiritual empowerment at Desa Punggul are enabled by two main factors. The first factor is the contribution of women organization (PKK). The women's organization promotes women's development in three areas: cognition (improving women's skills and knowledge, learning, or participating in decision-making, collaborating, and organizing community events), affection (boosting women's self-efficacy, self-worth, and strengthening women's mentality), and social (expanding social roles, establishing wider social relationships, and gaining support from their peers). The second component is the encouragement of a welcoming, cooperative, tolerant, engaging, and inclusive environment or community.